Wideband Microwave Absorber Comprising Metallic Split-Ring Resonators Surrounded With E-Shaped Fractal Metamaterial - R. M. H. Bilal (IEEE Access, 2021)
A specially designed metallic E-shaped fractal-based perfect metamaterial absorber (PMA) with fairly wideband absorptivity in the K- and Ka-bands of the microwave regime was investigated. The PMA top surface is comprised of square-shaped split-ring resonators (SRRs) surrounded with the stated fractal design. The absorptivity of PMA was analyzed in the range of 20 - 30 GHz for the normal and oblique incidence of waves. Both the transverse electric (TE) and transverse magnetic (TM) modes were taken up to observe the robustness of the proposed design. It was observed that the fractal resonators exhibit capacitive effect at low frequencies, whereas the SRRs manifest capacitive effect at higher frequencies. The simulation and measured results were found to be in fairly good agreement. It is expected that the proposed design of PMA would be useful for 5G communication applications.